Pengaruh penggunaan pembelajaran berdiferensiasi, expository dan motivasi belajar terhadap hasil belajar pada mata pelajaran matematika kelas 11 di sma giki – 1 surabaya - Sutini, Sutini; Fatirul, Achmad Noor; Prajitno, Sunyoto Hadi (UNDIKMA, 2025)
This study aims to examine the effect of the use of differentiated learning and learning motivation on student learning outcomes in Mathematics class XI at SMA GIKI – 1 Surabaya. The focus of the problems raised includes: (1) whether there is a significant influence between the use of differentiated learning compared to expository learning on Mathematics learning outcomes; (2) whether high and low levels of learning motivation affect student learning outcomes; and (3) whether there is an interaction between learning strategies and learning motivation on Mathematics learning outcomes. This study uses a quantitative approach with quasi experiment methods and 2x2 factorial design. The research sample consisted of students in grade XI of SMA GIKI-1 Surabaya who were selected through purposive sampling techniques. The instruments used include learning outcome tests to measure students' academic achievement and learning motivation questionnaires to classify students' motivation levels. The data obtained was analyzed using two-way ANOVA to determine the influence of each variable and its interactions. The results showed that: (1) there was a significant influence between the use of differentiated learning strategies on students' Mathematics learning outcomes compared to expository learning; (2) students with high learning motivation have better learning outcomes compared to students with low motivation; and (3) there is a significant interaction between learning strategies and the level of learning motivation on student learning outcomes. These findings indicate the importance of applying adaptive learning approaches and strengthening motivation in improving Mathematics learning achievement at the secondary education level.